Restriction of Mobile Phone Usage at Bed Time: Effect on Sleep Quality, Mood and Cognitive Function - Priyadharshini Sivagurunathan; Sasi Vaithilingan; Vinothkumar R (Medsci Publications, 2024)
Introduction: Mobile phones are integral to modern life, but excessive use, particularly at night, can lead to disrupt well-being. Limiting mobile phone use before bedtime may improve individual well-being. This study aimed to evaluate whether restricting mobile phone use at bedtime enhances sleep quality, mood, and cognitive function. Methodology: Undergraduate students from a selected engineering college were assessed for bedtime mobile phone use. Sixty-eight students were chosen via simple random sampling. A self-reported questionnaire including the Pittsburgh Sleep Quality Index, Positive and Negative Affect Scale, and Montreal Cognitive Assessment Scale evaluated sleep quality, mood, and cognitive function before implementing restrictions. The "Lock My Phone" app was used to enforce these restrictions. Post-intervention assessments were conducted on the 15th and 30th days. Results: Before the intervention, all students reported poor sleep quality, 80.8% had reduced positive affect, 91.1% experienced high negative affect, and only 23.5% had normal cognitive function. Significant improvements were observed in sleep quality, mood, and cognitive function post-restriction (p<0.001). Conclusion: Restricting mobile phone use before bedtime significantly improved sleep quality, mood, and cognitive function among undergraduate students.